Evaluation of the influence of therapeutic tasks performed by a nursing team on the quality of life of women after mastectomy - Stępień, Renata (Polish Journal of Public Health, 2010)
Aim. The aim of the research was to evaluate the satisfaction coming from therapeutic tasks performed by nurses and its influence on functional abilities of women after mastectomy, the radical treatment for breast cancer. Material and methods. he tested group consisted of 217 patients after radical surgical treatment for breast cancer. Functional Assessment Therapy Cancer Scale-Breast (FACT-B) by D.F. Cella and Nurse’s Therapeutic Tasks Assessment Scale, designed by the author of the study, were used in the research. Results. Nearly 62% of the respondents after radical surgical treatment for breast cancer assessed the value of the therapeutic tasks performed by nurses as high. The group of women who assessed the therapeutic procedures and measures taken by nurses as high, obtained significantly higher results in the sphere of family and social life (z = -3.216, p<0.01), complaints specific to breast cancer (z = -2.576, p<0.05) as well as general (z = -2.247,p<0.05) and global (z = -2.412, p<0.05) functioning. Conclusions. Only 2/3 of the patients assessed the quality of therapeutic tasks performed by nurses as high. Therefore, it is advisable to develop and improve professional competences in this aspect. The research shows a beneficial influence coming from a high level of satisfaction from therapeutic services provided by nurses on functional abilities of patients after mastectomy.